Complementary Practitioners’ View of Treatment for Inflammatory Bowel Disease - Marja J Verhoef; Ivan Rapchuk; Trina Liew; Vanessa Weir; Robert J Hilsden (Canadian Journal of Gastroenterology)
A substantial number of patients with inflammatory bowel disease use complementary therapies to manage their disease, including chiropractic and herbal therapies. The objective of this study was to explore whether providers of these therapies see patients with inflammatory bowel disease and recommend therapies, and to determine their opinions about the treatments that they recommend. The study sample comprised 66 chiropractors, 19 pharmacists, 16 herbalists and 15 health food store employees in Calgary, Alberta. A structured questionnaire containing two patient scenarios (a patient with active ulcerative colitis and a patient with inactive Crohn’s disease) was completed either by an in-person interview or by a mailed questionnaire. Most respondents had seen patients with ulcerative colitis, and at least 80% of each group except pharmacists (only 10%) would treat these patients or recommend treatment. Almost all chiropractors used spinal manipulation, whereas herbalists and health food store employees suggested a wide range of different treatments. Chiropractors rated their treatment as moderately effective; herbalists and health food store employees viewed their recommendations as very effective. The results with respect to the second scenario were very similar. The wide range of treatment recommendations by practitioners, who differ greatly in terms of skills, knowledge and experience, has important implications for physician-patient communication, information provision and education regarding complementary and alternative therapies.